A potential herbal component for the future treatment of fatty liver disease: Geniposide from gardenia - Zhang, Qinyao; Li, Ziyan; Wang, Lina (Frontiers in Pharmacology, 2025)
Nonalcoholic fatty liver disease (NAFLD) is a multisystemic metabolic disease whose global incidence is increasing annually; the currently available treatment options are limited to lifestyle alterations and symptomatic treatments, such as hepatoprotective treatments. However, it is difficult for most patients to adhere to strict lifestyle interventions for long periods, and lifestyle interventions alone have limited effects in some patients with moderate-to-severe NAFLD. Regarding traditional Chinese medicine (TCM) treatments, Zhi-Zi-Da-Huang decoction and Zhi-Zi-Huang-Qin decoction are widely used classic formulas for NAFLD. In this article, we present a review of the progress in research on the use of geniposide, the glycoside analog of gardenia, in the treatment of NAFLD. As a natural ingredient, geniposide has good safety and tolerability profiles and a high potential to exert pharmacological effects. We discuss various mechanisms of action of geniposide in the treatment of NAFLD, including decreased insulin resistance via the regulation of key molecules, such as insulin receptor substrate 1 (IRS-1) and glucose transporter type 1 (GLUT1), and the alleviation of oxidative stress via activation of the nuclear factor erythroid 2-related factor 2/heme oxygenase-1  (Nrf2/HO-1) signaling pathway. Geniposide also enhances mitochondrial function by inhibiting uncoupling protein 2 (UCP2)-mediated proton leakage and has anti-inflammatory and antiapoptotic effects. There are no previous studies reporting the various pharmacological mechanisms of geniposide in the treatment of NAFLD. Our study provides new insights into the effects and mechanisms of action of geniposide, but its toxicity, especially its hepatotoxicity, requires further investigation. Geniposide is a potential drug for the treatment of NAFLD, and further research and development are warranted.